Evidence for association of OCTN genes and IBD5 with ulcerative colitis. Issue 6 (16th December 2005) - Waller, S; Tremelling, M; Bredin, F; Godfrey, L; Howson, J; Parkes, M
Abstract : Background and aims: Genetic association between Crohn's disease (CD) and OCTN1 (SLC22A4) C1672T/OCTN2 (SLC22A5) G−207C variants in IBD5 has recently been reported. These genes encode solute carriers and the association was suggested to be distinct from the background IBD5 risk haplotype. There have been conflicting reports of the association between markers in the IBD5 region and ulcerative colitis (UC) and interaction (epistasis) between this locus and CARD15. Our aim was to ascertain the contribution of OCTN variants to UC and CD in a large independent UK dataset, to seek genetic evidence that the OCTN association is distinct from the IBD5 risk haplotype and to identify interactions between the IBD5 and CARD15 loci. Methods: A total of 1104 unrelated Caucasian subjects with inflammatory bowel disease (IBD) (496 CD, 512 UC, 96 indeterminate) and 750 ethnically matched controls were genotyped for three single nucleotide polymorphisms (SNPs) in the CD associated genes (OCTN1+1672, OCTN2−207, and IGR2230), and two flanking IBD5 tagging SNPs, IGR2096 and IGR3096. Data were analysed by logistic regression methods within STATA. Results: OCTN variants were as strongly associated with UC and IBD overall as they were with CD (p = 0.0001; OR 1.3 (95% confidence interval 1.1–1.5)). OCTN variants were in tight linkage disequilibrium with the extended IBD5 risk haplotype D′ 0.79 and 0.88, and r 2  = 0.62 and 0.72 for IGR2096 and 3096, respectively. There was no deviation from a multiplicative model of interaction between CARD15 and IBD5 on the penetrance scale. Conclusions: The OCTN variants were associated with susceptibility to IBD overall. The effect was equally strong in UC and CD. Although OCTN variants may account for the increased risk of IBD associated with IBD5, a role for other candidate genes within this extended haplotype was not excluded. There was no statistical evidence of interaction between CARD15 and either OCTN or IBD5 variants in susceptibility to IBD.